Pengelolaan Sistem Informasi Manajemen (SIM) RS di RSUD Kota Dumai Tahun 2021 - Zapri Salis; Doni Jepisah (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Management Information System is a computer-based system to process patient medical data and administrative data owned by the hospital. Based on the initial survey conducted in the field, all facilities and infrastructure supporting the use of SIMRS have not been fulfilled, such as computers, networks that have not been connected to all parts of the SIM RS installation. Residency method is qualitative using USG and Fishbone method. Informants in the residency amounted to 2 people with the subject of 1 person being the Head of the SIM Installation of the Hospital and 1 staff of the SIM Hospital. The results of the identification of the problem found that the facilities and infrastructure to support the use of the SIM Hospital were not yet optimal, the SPO in the SIM RS installation was not yet optimal, the implementation of tasks was not yet optimal in accordance with the organizational structure, the vision and mission of the SIM RS installation was still joined to the Vision and Mission of the Dumai City Hospital. The priority of the problem is that the facilities and infrastructure to support the use of the SIM Hospital are not met with a total score of 13. Recommendations It is hoped that an assessment of the Vision and Mission of the SIM Hospital should be made separately so that the objectives to be achieved from SIM installation, pay attention to infrastructure such as computers and internet networks for implementation. SIM RS which is integrated into all units, further clarifies the main tasks and functions of the RS SIM Installation, providing training related to the management of the RS SIM for HR in the SIM Hospital Installation.